Emergence of Citrobacter freundii carrying IMP‐8 metallo‐β‐lactamase in Germany. Issue 2 (20th March 2014) - Peter, S.; Wolz, C.; Kaase, M.; Marschal, M.; Schulte, B.; Vogel, W.; Autenrieth, I.; Willmann, M.
Abstract Metallo‐β‐lactamases (MBLs) in Enterobacteriaceae are an increasing problem worldwide. This report describes the isolation of Citrobacter freundii carrying IMP‐8 MBL from three patients during the period from March 2012 until March 2013 in Germany. The blaIMP‐8 enzyme is predominantly found in Asia, where IMP‐8 has spread to various enterobacterial species causing serious infections. To our best knowledge, this is the first report of blaIMP‐8 habouring Enterobacteriaceae in Europe.